Raw water quality variations and its effect on the water treatment processes. Issue 1 (31st December 2022) - Mensah-Akutteh, Hanson; Buamah, Richard; Wiafe, Samuel; Nyarko, Kwabena B.
Abstract: This research assesses the variation dynamics of contaminant loading in surface water and its effect on water treatment. A comparative analysis of the variations in physicochemical parameters of raw water quality and corresponding treated water was carried out using descriptive statistics, matrix correlation, and PCA multivariate statistical techniques. Monthly Panel/historical data between 2002 and 2016 from Ghana Water Company Limited (GWCL) treatment works (Adam Clark treatment plant) at Weija and physicochemical analysis of raw and treated water using plant simulation (Jar test) were employed. The highest variability was observed for colour, conductivity, and nutrient (COV;>40%), whilst pH, turbidity, alkalinity, and temperature had moderate variability (COV;<15%). Both natural and anthropogenic activities have a significant deterioration effect (p < 0.01) on the quality of the Weija lack, particularly anthropogenic activities (r = 0.491). Seasonal variation also affects the raw water quality. Consequently, the variations in the water quality parameters have a significant influence on the cost of the production of portable water. The results from this research should guide the Water Resources Commission on the remedial measures to be adopted to curtail the incessant pollution loading on surface water.